Multi-level Analyses of Accuracy and Error in Digital Criminal Record Data, Minnesota and New Jersey, 2017-2019 - Lageson, Sarah ([Verlag nicht ermittelbar], 2022)
This is a three-level analysis of digital criminal record information. Drawing from original mixed methods data involving 178 research participants, this study first describes individual-level qualitative data ("micro-level" results) describing experiences with digital criminal records, touching on issues of criminal record accuracy, digital reputation, and digital avoidance strategies. The second analysis examines nearly 5,000 criminal history events listed on participant's official state criminal records, which consist of official arrest and charging data. In this "meso-level" analysis, these 4,874 criminal history events are tracked across a broad set of public sector and private sector criminal record repositories. Results show how the record keeping practices of two states, Minnesota and New Jersey, translate into extralegal records that exist on the internet and in commercial databases. Further, this meso-level study details the thousands of criminal history events that originate outside state repositories, and instead appear first in commercial vendor databases or internet-based repositories (N=3,368). These erroneous or misleading records are likely the result of mismatched and misunderstood bulk data processing, but still pose practical problems for participants seeking employment, housing, and criminal record expungement. The final section, a "macro-level analysis" of criminal record disclosure, presents results from across the Unites States by reporting the disclosure practices of 200 criminal justice agencies, and estimates the volume of personally identifiable criminal record information disclosed each year on the internet. The current study release only contains the meso-level data.